Unlocking the potential of ponds and pondscapes as nature-based solutions for climate resilience and beyond: Hundred evidences - Bartrons, Mireia (2024)
Unlocking the full potential of ponds (small water bodies) and pondscapes (network of ponds) as Nature-based Solutions (NbS) is critical pursuit for enhancing ecosystems and societal resilience to climate change and other societal challenges. Despite scattered initiatives for pond/pondscape creation, restoration and management—each considered here a distinct NbS—there is a significant knowledge gap in utilising ponds/pondscapes as effective NbS. We aimed to assess these NbS in terms of their objectives, outcomes, effectiveness, multifunctionality, delivery of potentially conflicting effects, and the implementation process while considering their Nature´s Contributions to People (NCPs, i.e., benefits to society). We compiled data on 183 NbS actions implemented across 93 ponds/pondscapes from 24 countries, predominantly from Europe, via a questionnaire distributed to experienced stakeholders implementing NbS in ponds/pondscapes. One single pond/pondscape may imply more than one NbS action. Two-thirds were in rural areas, and one-third in urban settings. Our analysis revealed that Creation of habitat for biodiversity was a primary delivery objective (targeted NCP) in the implementation of most NbS in ponds/pondscapes, often also combined with other NCPs such as Learning and inspiration, Regulation of water quantity, and Physical and psychological experiences, showcasing their intended multifunctionality. Implemented NbS primarily focused on climate change adaptation (especially Regulation of hazards and extreme events, and water quantity) rather than mitigation, with less emphasis on measures like direct greenhouse gas emissions reduction or enhancing carbon sinks. The costs associated with pond´s NbS varied significantly depending on factors such as project scope, objectives, location, socio-economic-cultural system, and specific implementation requirements. The creation of ponds/pondscapes often entailed the highest financial investment, much more than their restoration or their management. In conclusion, our study underscores the multifunctionality of ponds/pondscapes and provides insights about their significant potential as cost-effective NbS for enhancing ecosystem and societal resilience to climate change and biodiversity. It underscores the importance of further research to fully understand and measure the diverse range of NbS they offer, particularly in the context of climate change mitigation. Standardised measurements of the NCP provided by these NbS in ponds/pondscapes are essential for validating managers´ claims and exploring their role in addressing climate change.